Studies in the archaeology and history of Caesarea Maritima : caput judaeae, metropolis palaestinae - Patrich, J. (Ancient Judaism and Early Christianity, 2011)
Caesarea Maritima, the capital of the Roman province of Judaea / Palaestina, was founded in 10/9 BCE by Herod the Great to serve as an administrative and economic center. It was named after his Roman patron Caesar Augustus, the first Roman emperor. The book, well illustrated, presents the results of the large scale excavations at the site during the 1990's and early 2000's in their wider historical and cultural context: the architectural evolution and transformation of the thriving city from its foundation to its decline caused by the Arab conquest (640/41 CE), its conversion to a Roman colony in 71 CE, aspects of provincial administration, commerce and economy, entertainment and religious life of its communities - Jews, Pagans, Christians and Samaritans.